Public Participation and Environmental management in Mountain National Parks - Stéphane Héritier (Revue de Géographie Alpine)
Public involvement has become a key concept in conservation management worldwide. This paper provides an overview of the situation in four countries where national parks have been established for over a century, and where their creation often involved clearing the land of earlier indigenous settlements. Since the 1970s, public participation has become common practice in park management, even though such participation has taken on a variety of forms. The paper analyses the general trends in public participation in park management practices, participation that most authors consider has contributed to successful governance policies and helped build participative democracy. Analyses at different levels, however, reveal that public participation can also divide stakeholders, making it really difficult for any effective coalition of stakeholders to emerge.